Biological characteristics of Muse cells derived from MenSCs and their application in acute liver injury and intracerebral hemorrhage diseases - Li, Han; Wei, Jinghui; Li, Mingzhi; Li, Yaoqiang; Zhang, Tong; Tian, Jialu; Liu, Xuejia; Li, Kangjia; Lin, Juntang (Regenerative therapy, 2024)
The increasing interest in multilineage differentiating stress-enduring (Muse) cells within the field of regenerative medicine is attributed to their exceptional homing capabilities, prolonged viability in adverse conditions, and enhanced three-germ-layer differentiate ability, surpassing their parent mesenchymal stem cells. Given their abundant sources, non-invasive collection procedure, and periodic availability, human menstrual blood-derived endometrium stem cells (MenSCs) have been extensively investigated as a potential resource for stem cell-based therapies. However, there is no established modality to isolate Muse cells from MenSCs and disparity in gene expression profiles between Muse cells and MenSCs remain unknown. In this study, Muse cells were isolated from MenSCs by long-time trypsin incubation method. Muse cells expressed pluripotency markers and could realize multilineage differentiation in vitro. Compared with MenSCs, Muse cells showed enhanced homing ability and superior therapeutic efficacy in animal models of acute liver injury (ALI) and intracerebral hemorrhage (ICH). Furthermore, the RNA-seq analysis offers insights into the mechanism underlying the disparity in trypsin resistance and migration ability between Muse and MenSCs cells. This research offers a significant foundation for further exploration of cell-based therapies using MenSCs-derived Muse cells in the context of various human diseases, highlighting their promising application in the field of regenerative medicine. •Muse cells derived from MenSCs are successfully obtained.•Muse cell has superior homing ability to inflammatory condition compared to MenSCs.•Muse cell exhibits greater effect for treating ALI and ICH diseases than MenSCs.•Differential gene analysis between Muse cells and MenSCs is conducted by RNA-seq.